Legal philosophy as practical philosophy - Vega, Jesús (Revus (Ljubljana), 2018)
My purpose in this paper is to make a case for the strictly philosophical nature of our discipline, legal philosophy. I first take a prior stance on the issue of what philosophy is in general and outline some premises for the definition of philosophical rationality. This then leads me to critically examine Bobbio's dichotomy between jurists' legal philosophy and philosophers' legal philosophy. It is essential to reformulate the relationships between legal philosophy as a "special" or "regional" discipline as opposed to "general" philosophy. So thirdly, I re-examine this problem using the distinction between concepts of law and ideas in law. Fourthly, I defend the thesis that, when ascertaining the type of philosophy the philosophy of law is, the most decisive factor is not so much (or not only) the relationship between philosophy of law and philosophy in general as, more importantly, the relationship between it and law itself. I argue that the nature of law itself makes its practice inevitably and ineluctably associated with philosophical ideas and conceptions. This practical view of law is tightly bound with a view of legal philosophy as a practical philosophy, and this is the main thesis I shall defend here. Different expressions of this practical view of law can be found in prominent contemporary authors who go beyond the dichotomy of legal positivism-natural law (such as Nino, Alexy, Dworkin, Atienza). The essential feature which I regard ties philosophy of law to the condition of some "practical philosophy" is the role played by the concept of value, i.e. the centrality and pre-eminence of its evaluative dimension.
Keywords: filozofija prava; jurisprudence; legal philosophy; legal positivism; legal post-positivism; legal theory; practical philosophy; praktična filozofija; pravni postpozitivizem; pravni pozitivizem; pravoslovje; teorija prava